Predição in silico e avaliação da atividade antinociceptiva de cumarinas e saponinas obtidas de plantas do semiárido em modelo de artrite induzida por zimosan - Silva, Bruno Cerqueira (2019)
Rheumatoid arthritis (RA) is a chronic inflammatory disease, considered a cause of temporary and / or definitive disability. The drugs available for its treatment induce numerous side effects, associated with a low efficacy and high cost to the patient. Therefore, the search for more efficient therapies, with lower cost and reduced unwanted effects, becomes a priority. It is in this context that this work evaluated the antinociceptive activity of four molecules isolated from plant species from the northeastern semi-arid region in an experimental model of RA induced by zymosan. Arthritis was induced in swiss male mice (n = 6) by administration of 30 μg/5 μl (i.a) zymosan at the right tibio-tarsal joint. The animals were treated with 1,2-benzopyrone (30, 60 and 90mg / kg), 7-hydroxycoumarin (30, 60 and 90mg / kg), hecogenin acetate (3, 10 and 30mg / kg) and diosgenin acetate 3, 10 and 30mg / kg) or vehicle 1 hour before the stimulus. Pretreatment with 1,2-benzopyrone, 7-hydroxycoumarin, hecogenin acetate and diosgenin acetate caused reduction of zymosan-induced hypernociception. From these results, molecular coupling routines with the enzymes cicloxigenase 1 and 2 (COX-1 and COX-2) and myeloperoxidase (MPO) were performed to evaluate the pattern of intermolecular interactions. The couplings showed that the compounds indicate relevance of hydrophobic interactions, salt bridges, hydrogen bonds and π stacking, important for the molecular recognition in the active site of the enzymes. The results demonstrate important pharmacological activity in the zymosan-induced arthritis tests evidencing by the molecular coupling technique an affinity of these compounds for COX-1 and COX-2 and MPO